Incidence of neurological complications following pediatric heart surgery and its association with neutrophil‐to‐lymphocyte ratio. Issue 1 (18th January 2023) - Abdshah, Alireza; Mirzaaghayan, Mohammadreza; Heidari, Morteza; Memarian, Sara; Amanollahi, Mobina; Nazeri, Azadeh; Gharib, Behdad
Abstract: Background and Aims: Due to increased rate of open‐heart surgeries in children, postsurgical mortality and morbidities have increasingly gained attention. Neurological complications are some of the most important postsurgical events. However, the number of studies regarding postsurgical neurological complications seems to be inadequate. We aimed to study the incidence of neurological complications following cardiac surgery in the pediatric cardiac intensive care unit (ICU) of the children's medical center. Methods: This cross‐sectional study was conducted from March to September 2019. We included all of the children who underwent cardiac surgery and were admitted to ICU at CMC. We collected their demographic data, lab test results (white blood cell count, absolute neutrophile and lymphocyte counts) and calculated their Risk Adjustment for Congenital Heart Surgery (RACHS) score. We then documented neurological adverse events and investigated the associations between those events and the patients' data. Results: Of the 267 studied patients, 14 developed neurological complications (5.2%); seven developed chorea (2.6%), four developed seizures (1.5%), and two developed both seizure and chorea (0.7%). One case developed subarachnoid hemorrhage (SAH). We observed that age ( p  = 0.000), weight ( p  = 0.000), and RACHS score ( p  = 0.006) were associated with the development of neurological complications. Additionally, we observed that "neutrophil to lymphocyte ratio" was not associated with the risk of postsurgical neurological complications. Conclusion: Younger age, lower weight, and higher RACHS score were associated with neurological complications after operations. Given the importance of postsurgical neurological complications, further investigations should be carried out to cover this issue and discover preventive strategies for such morbidities.